Ecosystem Services Becoming Political: How Ecological Processes Shape Local Resource-Management Networks - Kuslits, Béla; Vári, Ágnes; Tanács, Eszter; Aszalós, Réka; Drasovean, Anghel; Buchriegler, Regina; Laufer, Zsanett; Krsic, Damir; Milanovic, Ranko; Arany, Ildikó (Frontiers in Ecology and Evolution, 2021)
While a landscape usually provides a wide range of benefits, the ecological and spatial entanglement of the processes behind ecosystem services does not allow maximizing benefits from all services at the same time. Different stakeholders relying on different services might therefore prefer different policies and management for the wider area where they operate. Trade-offs, disagreements and mutual interests are rooted in ecological processes but are manifested in the social sphere. Social networks were shown to have a significant impact on the management of ecosystem services. In this paper we show that ecosystem services also influence the structure of management-networks and power-relations among stakeholders, thus ecological factors set the stage for (local-regional) political discourse. We used social network analysis to show how ecological processes become agents of social-ecological systems, this method is also useful for finding those players who can adopt a mediator role in the social sphere, having a special position in the web of competing interests. Our research shows how mutual influence between social and ecological elements shapes management strategies in five protected areas in Central and Eastern Europe. The most voluminous and profitable ecosystem services (primarily timber production in our cases) define which stakeholders are the most powerful in management networks – this eminent position allows these players to make decisions unilaterally. Other, smaller players tend to negotiate with a diverse set of counterparts with whom they share and co-manage often multiple services. Power relations that emerge as a consequence of production differences among ecosystem services often do not allow participatory management methods. These situations lead to over-utilization of natural resources with a narrow interpretation of sustainability which decreases resilience for the whole social-ecological system. Our results contribute to the theoretical understanding of political discourses in social-ecological systems and showcase how social network analysis can be applied as a tool to facilitate participatory landscape-management. We show how ecological factors co-create the social sphere where decisions are made about sustainable land-use.